Unveiling unique endemic associations: A contribution to the knowledge of chasmophytic vegetation on the Sorrento Peninsula and Picentini Mountains - La Montagna, Dario; Ammann, Emile; Buttarazzi, Francesco; Cambria, Vito Emanuele; Caucci, Lorenzo; De Luca, Elisa; De Sanctis, Michele; Frasca, Sara; Attorre, Fabio; Fanelli, Giuliano (Hacquetia, 2024)
Sorrento Peninsula, together with an outpost at the top of the Picentini Mountains, is rich in local endemics and has been well studied from a taxonomical perspective. The vegetation is instead poorly known, particularly the plant assemblages of rock cliffs. In this paper, we present the phytosociological insights on cliff-dwelling communities of rocky ranges in the top of Sorrento Peninsula (600-1800 m a.s.l.). We carried out 28 relevés (8 already published) and conducted multivariate analyses to classify the vegetation. We analysed the bioclimatic context of the relevés with Rivas-Martínez indexes and carried out a comparison with other rock vegetation from the Central Mediterranean. We found three clusters that we classified into 2 associations, one of which is further divided into two sub-associations (Globulario neapolitanae-Loniceretum stabianae typicum Fanelli et al. 2020; Globulario neapolitanae-Loniceretum stabianae globularietosum neapolitanae subass. nova; Diantho virginei-Seselietum polyphylli ass. nova). We refer this vegetation to a new alliance, Lonicerion stabianae all. nova, distinguished from the other rock vegetation of the Central Mediterranean because develops in an intermediate range between the mediterranean, temperate and weakly continental climate. Sorrento Peninsula and the cliffs at the top of Picentini Mountains are characterised by endemic cliff vegetation, rich in exclusive taxa. We suggest that it represents a distinct phytogeographical sector in the context of the Italian Peninsula.